Languages of the World: Mande languages - (:unkn) unknown (My University, 2017)
The book continues the encyclopaedic multi-volume publication “Languages of the World”, which is being prepared at the Institute of Linguistics of the Russian Academy of Sciences. This volume is dedicated to the Mande languages spoken in the Western sub-Saharan Africa. A large part of the articles represent very first descriptions of the respective languages based on the field data collected by the authors. Each description follows the typologically-oriented template implemented throughout the “Languages of the World” volumes. A set of maps illustrating the geographic distribution of the Mande languages is appended to the volume. The book is addressed to a broad audience of linguists, historians, and cultural anthropologists, as well as anyone interested in African languages.
Keywords: African Research